Qatari GLAMs and their Role in Activating and Enhancing Soft Power - Alya bint Ahmed Al Thani (15443944) (2023)
This presentation was given by Her Excellency Sheikha Alya bint Ahmed Al Thani, Ambassador of Qatar to the United Nations